Strikingly diverse reactivity of structurally identical silylene and stannylene - Parvin, Nasrina; Dasgupta, Rajarshi; Pal, Shiv; Sen, Sakya S.; Khan, Shabana (Dalton Transactions, 2017)
The reactivity of structurally identical silylene and stannylene [PhC(NtBu)(2)EN(SiMe3)(2)] (E = Si (1) and Sn (2)) towards coinage metals has been explored. While 1 has the propensity to form an adduct with coinage metals (4 and 5), 2 undergoes a ligand exchange reaction with copper halides and silver triflate leading to PhC(NtBu) 2SnX (X = Br (6), Cl (7), and OSO2CF3 (8)) with concomitant formation of [M{N(SiMe3) (2)}] (M = Cu, Ag). However, with AgSbF6 both 1 and 2 led to ion pairs, 9(+) .SbF(6)(-)and 10(+) . SbF(6)(-)displaying weaker Ag center dot center dot center dot center dot F interactions in the latter.

Synthesis and application of silylene-stabilized low-coordinate Ag(I)-arene cationic complexes - Parvin, Nasrina; Sen, Nilanjana; Tothadi, Srinu; Muhammed, Shahila; Parameswaran, Pattiyil; Khan, Shabana (Organometallics, 2021)
We report the first examples of N-heterocyclic silylene-stabilized monocoordinate Ag(I) cationic complexes weakly bound to the free arene rings (C6H6, C6Me6, and C7H8). Further, the application of these electrophilic Ag(I) complexes as catalysts has been investigated toward A(3)-coupling reactions, which afforded a series of propargylamines in good to excellent yields with low catalyst loading under a solvent-free condition (19 examples).

Silylene-copper(i) catalysis: regioselective protoboration of terminal alkynes - Kaulage, Sandeep H.; Shah, Brij Kumar; Panday, Rishukumar; Sharma, Himanshu; Vanka, Kumar; Khan, Shabana (Chemical Communications, 2025)
Herein, we report an efficient regioselective protoboration of the terminal alkynes catalyzed by newly synthesized silylene-copper(i)-aryl complexes. This method offers a broad substrate scope, good functional-group compatibility, and a gram-scale synthetic ability. The insight into the mechanistic cycle is also provided with the support of experimental and theoretical studies.